KEPUTUSAN SUMBER PEMBELANJAAN PADA USAHA MIKRO KECIL MENENGAH (UMKM) SWALAYAN DI DESA MULYOAGUNG KECAMATAN DAU MALANG - M. Abdimas Haidar Rahbany (Manajemen Bisnis, 2015)
The purpose of this study was to determine the source of funds used in the micro and small businesses in the village supermarket Mulyoagung District of DAU. The method used is the method of survey, data analysis is qualitative descriptive analysis based on primary and secondary data. Based on the results of a survey conducted by the researchers of the 10 self-service according to the class of micro enterprises in the village Mulyoagung DAU Malang, there is a 100% initial planning. the source of funds used for micro and small businesses in the supermarket, the source of funds used approximately 75.5% use their own capital due, which was developed in the supermarket business is already quite big and cost quite a lot. Supermarkets that require considerable cost using capital loans at the bank around 24.5% to run a business in this way could make more developed self.